2020
DOI: 10.1007/s40314-020-1104-1
|View full text |Cite
|
Sign up to set email alerts
|

The elastic boundary value problem of extended modified Bessel equation and its application in fractal homogeneous reservoir

Abstract: By introducing the elastic boundary value condition, the elastic boundary value problem of extended modified Bessel equation is proposed, we can use the following method to solve it. First, two linear independent solutions of extended modified Bessel equation are obtained. Second, the generating function of solution is constructed. Third, the kernel function of solution is constructed using the elastic right value condition. Finally, the solution is obtained by assembling coefficients with the left boundary va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…( 9), the general solution can be converted into: On substituting Eqs. (61) and (62) into the system of ordinary differential equations and using the differential property of linearly independent combination [4,23], The following equation is obtained:…”
Section: Appendix B (Derivation Details)mentioning
confidence: 99%
See 2 more Smart Citations
“…( 9), the general solution can be converted into: On substituting Eqs. (61) and (62) into the system of ordinary differential equations and using the differential property of linearly independent combination [4,23], The following equation is obtained:…”
Section: Appendix B (Derivation Details)mentioning
confidence: 99%
“…In recent three years, the elastic outer boundary conditions have been applied to the reservoir seepage model [3,4], replacing the three special outer boundary conditions commonly used before. The results show that the elastic outer boundary conditions can better reflect the real situation of the reservoir than the special outer boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model solving steps were simplified, and the influence of different parameters on the dimensionless bottom hole pressure and its derivative was analyzed. In 2019, Li et al [21] aimed at the idealization of the external boundary conditions (infinite, constant pressure, closed) of the traditional fractal homogeneous reservoir model, introduced the elastic external boundary conditions, and the fractal homogeneous reservoir seepage model was established. It was found that the elastic external boundary is located between the three ideal state boundaries, which can more truly reflect the seepage law.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers studied the fluid flow characteristics of the reservoirs with the EOB. Li et al [65] studied the seepage model for the homogeneous reservoir by introducing the EOB, and Li et al [66] discussed an elastic boundary value problem of the extended modified Bessel equation introducing the elastic boundary value condition, established the seepage model for fractal homogeneous reservoirs with the EOB, and obtained its solution. Kim et al [67] built the well-testing model for the DPRs with the EOB 2 Geofluids considering skin and wellbore storage and introducing effective well radius, and Zheng et al [68] established the dualporosity media seepage model for shale reservoirs with the EOB taking the adsorption and desorption processes into account.…”
Section: Introductionmentioning
confidence: 99%